2003
DOI: 10.1159/000072309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Food Restriction on Cold-Induced Thermogenesis in the Offspring

Abstract: Food restriction imposed during pregnancy usually leads to many alterations in the development of the conceptus. Some of these alterations can be reverted after birth by adequate nutritional rehabilitation, while there are others which are permanent. The aim of this article is to study the influence of maternal food restriction on offspring thermoregulation. Offspring of dams with food restriction during pregnancy (50%) were fed ad libitum after weaning. Rectal temperature was measured every 15 days from weani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
(40 reference statements)
2
6
0
Order By: Relevance
“…It is interesting that plasma corticosterone concentrations remained somewhat elevated even after 4 days of sleep recovery, which could, at least in part, explain the maintenance of altered body composition. Similar alterations in body composition are described for cold-acclimated animals, in which fat deposits are mobilised to compensate for cold-induced thermogenesis (32), resulting in diminished fat content and increased water percentage in the carcass, as previously described by Le Blanc et al (33).…”
Section: Discussionsupporting
confidence: 77%
“…It is interesting that plasma corticosterone concentrations remained somewhat elevated even after 4 days of sleep recovery, which could, at least in part, explain the maintenance of altered body composition. Similar alterations in body composition are described for cold-acclimated animals, in which fat deposits are mobilised to compensate for cold-induced thermogenesis (32), resulting in diminished fat content and increased water percentage in the carcass, as previously described by Le Blanc et al (33).…”
Section: Discussionsupporting
confidence: 77%
“…The present study showed that the offspring of food-restricted dams exhibited lower body weight than those of control dams. These results replicate previous findings from our group (Luz and Griggio, 1996;Griggio et al, 1997;Luz et al, 2003), and suggest that the mother transfers part of her nutritional deficit to the offspring in order to keep survival.…”
Section: Discussionsupporting
confidence: 91%
“…Previous study from our laboratory has shown that the offspring of food-restricted mothers exhibits difficulty in maintaining their body temperature over a longer period of time after birth, but after adjusting their thermoregulatory mechanisms they are able to maintain body temperature even in cold environment (Luz et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…Fetal adipose tissue deposition occurs mostly during the last trimester of gestation, over the period of maximal fetal and placental growth, and depends heavily on nutritional constraints. Unlike other fetal organs, which are unaffected by nutritional restriction, fat mass can be significantly altered by changes in maternal and fetal nutrition (Budge et al 2003;Luz et al 2003;Symonds et al 2003Symonds et al , 2004Larciprete et al 2005).…”
Section: Temporary Maternal Malnutritionmentioning
confidence: 99%